2022
DOI: 10.1039/d2ta04901e
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet-printed transparent micro-supercapacitors with morphology tailored co-continuous mesoporous Mn3O4

Abstract: High energy density, flexible supercapacitors typically use various carbon allotropes and 2-dimensional metals as the electrode material. As an alternative, here we report, fully printed, bendable and high-capacity micro-supercapacitors (MSCs)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…10d). 61,[62][63][64] The IPN-CNT construct was glued onto a flexible substrate and together had a thickness of 0.3 mm. Therefore, the maximum strain at the outer surface was 1.5% and mostly tensile in nature, along its cross-section (as the IPN-CNT construct was placed at the outer surface).…”
Section: Mechanical Robustnessmentioning
confidence: 99%
“…10d). 61,[62][63][64] The IPN-CNT construct was glued onto a flexible substrate and together had a thickness of 0.3 mm. Therefore, the maximum strain at the outer surface was 1.5% and mostly tensile in nature, along its cross-section (as the IPN-CNT construct was placed at the outer surface).…”
Section: Mechanical Robustnessmentioning
confidence: 99%
“…Mn 3 O 4 is gaining attention as a pseudocapacitive charge-storage material for supercapacitors. Investigations focused on the fabrication of thin films and high-active-mass (AM) bulk electrodes , by various techniques and analysis of the charging mechanism. The investigation of Mn 3 O 4 behavior in a Na 2 SO 4 electrolyte is of particular importance for the manufacturing of asymmetric supercapacitors for operation in the voltage range of 1.6–2.0 V. The first step of the charging mechanism in a Na 2 SO 4 electrolyte involves solvation: Mn 3 normalO 4 Na δ MnO italicx · normalH 2 normalO X-ray absorption spectroscopy (XAS) investigations confirmed Na δ MnO x formation during the initial cycling and revealed Mn 3+ -ion reduction. Another XAS study confirmed the reduction of Mn 3+ to Mn 2+ at low potentials and revealed the oxidation of Mn 3+ to Mn 4+ or Mn 6+ at higher potentials …”
Section: Introductionmentioning
confidence: 99%
“…1−4 Recently, an area of transparent power sources has emerged as a new field of research to satisfy such energy demands. 5 On the other hand, the continuous research efforts toward faster processing and reduction in circuit dimensions are making it increasingly important to find energy solutions to power these new and evolving electronic and optoelectronic devices and systems. Microbatteries and microsupercapacitors (MSCs) are the two promising candidates that can fulfill most of the above-mentioned criteria.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The developments in consumer optoelectronics, smart glasses/windows, interactive and invisible electronics, electronic skins, etc., are driving an increasing demand for reliable, ultrasmall, lightweight, inexpensive, highly efficient, as well as optically transparent power sources. Recently, an area of transparent power sources has emerged as a new field of research to satisfy such energy demands . On the other hand, the continuous research efforts toward faster processing and reduction in circuit dimensions are making it increasingly important to find energy solutions to power these new and evolving electronic and optoelectronic devices and systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation